A Study On The Compatibility Of Pathway To English For Grade X Based On The 2013 Curriculum - Nurhidayah, Okta; , Drs. Djoko Srijono, M.Hum; , Mauly Halwat, Ph.D (2015)
This study is focused on the compatibility of Pathway to English forGrade X with the 2013 curriculum. This study is aimed to describe whether or not the textbook is suitable with the syllabus of the 2013 curriculum by giving percentage from the total materials in the textbook based on Sadiman's theory and make a "Schema of Quality Classification" based on Suharsimi's theory. This is a descriptive qualitative analysis. The object of this study is the material of the textbook entitled "Pathway to English" for Grade X published by Erlangga. The technique of collecting data is documentation analysis. There are several procedures of collecting data such as finding out the English materials provided in the textbook, classifying the materials, coding the data, comparing the English materials in the textbook with the syllabus of the 2013 curriculum, and counting percentage. The data are analyzed by counting percentage (Sadiman's theory) and using schema of quality classification (Suharsimi's theory). The results of this study show thatthe total percentage of observing is 36,36%, communicating is 6,16%, questioning is 6,16%, and negotiating is 16,55%. The conclusion is the tasks in the textbook of Pathway to English for Grade X are included as Poor because the interval percentage is less than 40%. Keywords:compatibility, textbook, the 2013 Curriculum.